Economic effects of fundamental tax reform - Aaron, Henry J.; Gale, William G. (Brookings Institution Press, 1996)
The tax system profoundly affects countless aspects of private behavior. It is a powerful policy influence on the distribution of income and it is the one aspect of government that almost every citizen cannot avoid. With tax reform high on the political agenda, this book brings together studies of leading tax economists and lawyers to assess the various reform proposals and examine the effects of tax reform in several distinct areas. Together, these studies and comments on them present a balanced evaluation of professional opinion on the issues that will be critical in the tax reform debate. T.